Pengembangan e-Modul Berbasis Model Experiential Learning pada Materi Pencemaran Lingkungan untuk SMP Kelas VII: The Development of e-Modules Based on Experiential Learning Models on Environmental Pollution Materials for Class VII Middle Schools - Novti Lastri; Afreni Hamidah; M. Haris Effendi Hsb (Universitas Jambi, 2019)
Some factors affect student's low understanding of learning material such as the rare use of instructional media as well as the lack of alternative learning resources. Therefore, we carried out research and development of e-Modules based on experiential learning on environmental pollution material for junior high school. The research used ADDIE framework, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study covers the subject of water, air, and soil pollution. The theoretic feasibility of the e-Modules obtained through validation by the material and media validators. The validations were done twice and reach a value of 86.15% for the material aspect and 85.71% for the media aspect (both are in the very valid category). The practical feasibility of the e-Modules was measured through the perception response of educators (85.38%), in one-on-one trials (85%), small group trials (84.16%), and large group trials at SMPN 30 Merangin and SMPN 3 Kota Jambi (85.76% and 85.12% respectively). All result of the questionnaire was in the excellent category. The result of a large group trial obtained a Cohen's Kappa coefficient of 0.499 with a significant value of 0.000. Based on Kappa interpretation table, the value of 0.41 to 0.60 (a quite strong category). The e-Module based on experiential learning on environmental pollution material is appropriate for junior high school teaching material.